Percepciones del paisaje, una mirada de la belleza escénica en el paisaje cultural cafetero de Risaralda (Colombia) - Ramírez Arias, Sebastián
Despite not being considered as a patrimonial attribute of the Coffee Cultural Landscape, the scenicbeauty of this territory is a fundamental part of the sense of place that identifies its inhabitants.However, this landscape does not have systematic studies aimed at informing about its visualattributes and how these are perceived by the subjects. Therefore, the work reports the results of asurvey that sought to relate the scenic beauty perceived by the participants with attributes regardedin the literature as predictors of preference, evaluating the levels of maintenance, complexity andnaturalness of 20 viewsheds corresponding to declared areas as a World Heritage Site by UNESCO ineleven municipalities of the department of Risaralda, Colombia. The study found that the visualattribute with the greatest explanatory power is maintenance, represented in the landscape by signsof care, defined geometries, soft textures and differentiable shapes. This preference is explainedfrom the similarity of the viewsheds with the idealized image of the coffee landscape, highlightingthe need for subsequent research efforts that account for the visual attributes associated with thenatural values of the landscape, as a means of defining heritage management guidelines of thelandscape that can transcend the established aesthetic canon